EFEKTIVITAS PEMBELAJARAN MENULIS TEKS EDITORIAL MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN NEARPOD PADA SISWA KELAS XII - Siti Aisyah; Nurhayati, Enung; Wuriyani, Woro (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study began with the problem of students struggling to write editorial texts. This difficulty arose due to the conventional teaching methods used by teachers and the limited use of innovative learning media. To address this issue, the researcher employed an innovative teaching model, Problem-Based Learning, assisted by Nearpod. The study aimed to determine the effectiveness of editorial text writing learning using Problem-Based Learning assisted by Nearpod. The research used a quantitative approach and an experimental method with a one-group pretest-posttest design. The results showed that the average pretest score was 65, while the posttest score was 85. The results indicated that the p-value was less than 0.05, which falls within the acceptance range of Ha (0.000 < 0.05). Therefore, Ha was accepted and Ho was rejected. Based on the N-Gain test results, the score obtained was 0.56, which falls within the moderate category. Thus, Problem-Based Learning assisted by Nearpod is deemed effective in improving the learning outcomes of writing editorial texts.